Brain structure mediates the association between socioeconomic status and attention‐deficit/hyperactivity disorder. Issue 1 (27th May 2019) - Machlin, Laura; McLaughlin, Katie A.; Sheridan, Margaret A.
Abstract: Low socioeconomic status (SES) is associated with greater risk for symptoms of attention‐deficit/hyperactivity disorder (ADHD). One mechanism through which SES may confer risk for ADHD is by influencing brain structure. Alterations to cortical thickness, surface area and subcortical volume have been associated with low SES and with the presence of ADHD across multiple studies. The current study examined whether cortical thickness, surface area or subcortical volume mediate the associations between SES and ADHD in youth 3–21 years old ( N = 874) from the Pediatric Imaging, Neurocognition and Genetics Study. Freesurfer was used to estimate cortical thickness, surface area and subcortical volume from structural magnetic resonance imaging. Parents reported on demographics, family SES, ADHD diagnoses and the presence of child attention problems. Statistical mediation was assessed using a bootstrap resampling procedure. Controlling for parental ADHD, child age, gender, birth weight and scanner, children in low SES families were more likely to be in the ADHD group. Consistent with previous reports in this sample, low SES was associated with reduced surface area across the frontal lobe and reduced subcortical volume in the amygdala, cerebellum, hippocampus and basal ganglia. Of these regions, a significant indirect effect of SES on ADHD status through subcortical volume was observed for the left cerebellum (95% confidence interval: 0.004, 0.022), the right cerebellum (95% confidence interval: 0.006, 0.025), and the right caudate (95% confidence interval: 0.002, 0.022). Environmentally mediated changes in the cerebellum and the caudate may be neurodevelopmental mechanisms explaining elevated risk of ADHD in children in low SES families. Abstract : The study examined the relationship between family socioeconomic status, alterations in brain structure, and ADHD status in youth. Subcortical volume in the cerebellum and the caudate mediated the relationship between low socioeconomic status and ADHD in children.